2‐Amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine (PhIP)‐DNA adducts in benign prostate and subsequent risk for prostate cancer. Issue 4 (9th March 2013) - Tang, Deliang; Kryvenko, Oleksandr N.; Wang, Yun; Trudeau, Sheri; Rundle, Andrew; Takahashi, Satoru; Shirai, Tomoyuki; Rybicki, Benjamin A.
<x xml:space="preserve">Abstract</x> Despite convincing evidence that 2‐amino‐1‐methyl‐6‐phenylimidazo[4, 5‐b]pyridine (PhIP)—a heterocyclic amine generated by cooking meats at high temperatures—is carcinogenic in animal models, it remains unclear whether PhIP exposure leads to increased cancer risk in humans. PhIP‐DNA adduct levels were measured in specimens from 534 prostate cancer case‐control pairs nested within a historical cohort of men with histopathologically benign prostate specimens. We estimated the overall and race‐stratified risk of subsequent prostate cancer associated with higher adduct levels. PhIP‐DNA adduct levels in benign prostate were significantly higher in Whites than African Americans (0.274 optical density units (OD) ±0.059 vs. 0.256 OD ±0.054; p<0.0001). Prostate cancer risk for men in the highest quartile of PhIP‐DNA adduct levels was modestly increased [odds ratio (OR) = 1.25; 95% confidence interval (CI) = 0.76–2.07]. In subset analyses, the highest risk estimates were observed in White patients diagnosed more than 4 years after cohort entry (OR = 2.74; 95% CI = 1.01–7.42) or under age 65 (OR = 2.80; 95% CI = 0.87–8.97). In Whites, cancer risk associated with high‐grade prostatic intraepithelial neoplasia combined with elevated PhIP‐DNA adduct levels (OR = 3.89; 95% CI = 1.56–9.73) was greater than risk associated with either factor alone. Overall, elevated levels of PhIP‐DNA adducts do not significantly increase prostate cancer risk. However, our data show that White men have higher PhIP‐DNA adduct levels in benign prostate tissue than African American men, and suggest that in certain subgroups of White men high PhIP‐DNA adduct levels may predispose to an increased risk for prostate cancer.